PUBLIC SAFETY IN CRIMINAL-LEGAL CONTEXT (MONITORING INNOVATION) - Almas Kanatovich Канатов; Erbolat Елубай (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
In the article reviewed the qualification problems of individual criminal offenses (Criminal code of the Republic of Kazakhstan articles 279 and 280). Offering detailed scientific comments.